2005
DOI: 10.1007/s11101-005-3754-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Pharmacology of Gynostemma pentaphyllum

Abstract: In traditional Chinese medicine, Gynostemma pentaphyllum (Thunb.) Makino is a herbal drug of extreme versatility and has been extensively researched in China. The dammarane saponins isolated from Gynostemma pentaphyllum, namely gypenosides or gynosaponins, are believed to be the active components responsible for its various biological activities and reported clinical effects. This review attempts to encompass the available literature on Gynostemma pentaphyllum, from its cultivation to the isolation of its chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
116
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 58 publications
0
116
0
2
Order By: Relevance
“…Total extracts or saponins from this plant have been shown to exert a wide range of beneficial effects such as reducing cholesterol and blood glucose levels, strengthening immunity, and inhibiting cancer growth (13)(14)(15)(16). These activities likely overlap with diverse downstream effects on AMPK activation (9).…”
Section: Introductionmentioning
confidence: 99%
“…Total extracts or saponins from this plant have been shown to exert a wide range of beneficial effects such as reducing cholesterol and blood glucose levels, strengthening immunity, and inhibiting cancer growth (13)(14)(15)(16). These activities likely overlap with diverse downstream effects on AMPK activation (9).…”
Section: Introductionmentioning
confidence: 99%
“…Gypenosides also showed a protective effect on dopaminergic neuronal cell death in the MPTP-induced rat model of PD (Wang et al, 2010). It has been shown that GP-BX has several gypenoside derivatives, including gynosaponin TN-1, gynosaponin TN-2, gypenoside XLV, and gypenoside LXXIV (Choi et al, 2010;Razmovski-Naumovski et al, 2005;Nagai et al, 1981;Takemoto et al, 1984;Yoshikawa et al, 1987). These data further support that GP-BX can be applied for the prevention of the symptoms of PD by scavenging the formation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various bioactive functions of GP, it has been known to have anti-oxidant, anti-inflammatory, and immunostimulatory actions (Razmovski-Naumovski et al, 2005). In addition, GP ethanol extract has been found to have an anti-stress function against chronic EF stress in mice (Choi et al, 2008;Im et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…콜라겐 양의 감소가 피부 주름 생성의 주요 원인으로 인식되면서 콜라겐 합성을 촉진할 수 있는 항노화 물 질의 개발에 많은 노력이 모아지고 있다 [4,5]. 돌외(Gynostemma pentaphyllum Makino)는 박과 (Cucurbitaceae)의 다년생 덩굴 식물로 우리나라 남부 와 아시아 지역에 분포되어 있다 [6]. 돌외의 주요 성분 은 dammarane 타입의 트리터펜(triterpene) 배당체 화 합물인 gypenoside이며 100여 종이 분리되어 보고되고 있다 [7].…”
unclassified